Answer:
Explanation:
Given:
∠2 ≅ ∠7 ≅ ∠19
m∠2 = 125°
Since, m∠1 + m∠2 = 180° [Linear pair of angles]
m∠1 + 125° = 180°
m∠1 = 180 - 125 = 55°
m∠1 = m∠3 = 55° [Vertically opposite angles]
m∠2 = m∠4 = 125° [Vertically opposite angles]
m∠5 = m∠7 = 125°
m∠5 + m∠6 = 180° [Linear pair of angles]
125° + m∠6 = 180°
m∠6 = 180 - 125 = 55°
m∠7 = m∠5 = 125°
m∠8 = m∠6 = 55°
m∠19 = m∠17 = 125° [Vertically opposite angles]
m∠19 + m∠18 = 180° [linear pair of angles]
125° + m∠18 = 180°
m∠18 = 55°
m∠18 = m∠20 = 55° [Vertically opposite angles]
m∠13 = m∠20 = 55° [Corresponding angles]
m∠16 = m∠17 = 125° [Corresponding angles]
m∠15 = m∠18 = 55° [Corresponding angles]
m∠14 = m∠19 = 125° [Corresponding angles]
m∠13 + m∠10 + m∠8 = 180° [Sum of angles in a triangle]
55° + m∠10 + 55° = 180°
m∠10 = 180 - 110 = 70°
m∠10 = m∠12 = 70° [Vertically opposite angles]
m∠9 + m∠10 = 180° [Linear pair of angles]
m∠9 = 180 - 70 = 110°
m∠11 = m∠9 = 110° [Vertically opposite angles]